The Development and Change in City Branding: A Content Analysis of the Literature - Senay Oguztimur; Ulun Akturan (European Regional Science Association (ERSA), 2014)
The purpose of this study is to systematically review the city branding literature to provide an explicated and organized view and highlight further research opportunities. In that sense, the articles published on "city branding" and "city marketing" between 1988 and 2014 were explored via content analysis. The analysis of 146 articles suggests that there is a growing interest from different disciplines for city branding as a research domain. Therefore, it is concluded that, city branding is a multi-disciplinary area. There is a wide array of journals that are interested in and published articles on city branding. However, especially, the domain-specific journals contributed most that research area to develop. It was found that that 102 different cities from 38 different nations are studied and comparison among the cities are highly common. Most of the studies are research based and qualitative methods and case study approach are commonly used. However, there is a general tendency to describe the data but not interpret the relations between the concepts and theories. Therefore the knowledge is idiographic. Even if there is a western domination, the worldwide geographical coverage is
Keywords: M31; R00; 330